Impact of Smoking Status on Mortality in STEMI Patients Undergoing Mechanical Reperfusion for STEMI: Insights from the ISACS-STEMI COVID-19 Registry - De Luca, Giuseppe; Algowhary, Magdy; Uguz, Berat; Oliveira, Dinaldo C; Ganyukov, Vladimir; Zimbakov, Zan; Cercek, Miha; Jensen, Lisette Okkels; Loh, Poay Huan; Calmac, Lucian; Ferrer, Gerard Roura I; Quadros, Alexandre; et al. (Journal of clinical medicine, 2022)
The so-called “smoking paradox”, conditioning lower mortality in smokers among STEMI patients, has seldom been addressed in the settings of modern primary PCI protocols. The ISACS−STEMI COVID-19 is a large-scale retrospective multicenter registry addressing in-hospital mortality, reperfusion, and 30-day mortality among primary PCI patients in the era of the COVID-19 pandemic. Among the 16,083 STEMI patients, 6819 (42.3%) patients were active smokers, 2099 (13.1%) previous smokers, and 7165 (44.6%) non-smokers. Despite the impaired preprocedural recanalization (p < 0.001), active smokers had a significantly better postprocedural TIMI flow compared with non-smokers (p < 0.001); this was confirmed after adjustment for all baseline and procedural confounders, and the propensity score. Active smokers had a significantly lower in-hospital (p < 0.001) and 30-day (p < 0.001) mortality compared with non-smokers and previous smokers; this was confirmed after adjustment for all baseline and procedural confounders, and the propensity score. In conclusion, in our population, active smoking was significantly associated with improved epicardial recanalization and lower in-hospital and 30-day mortality compared with previous and non-smoking history.
Keywords: myocardial infarction; COVID-19; percutaneous coronary intervention; smoking paradox